Correction: Twisted-graphene-like perylene diimide with dangling functional chromophores as tunable small-molecule acceptors in binary-blend active layers of organic photovoltaics. Issue 38 (27th September 2021) - Lin, Yu-Che; Chen, Chung-Hao; She, Nian-Zu; Juan, Chien-Yao; Chang, Bin; Li, Meng-Hua; Wang, Hao-Cheng; Cheng, Hao-Wen; Yabushita, Atsushi; Yang, Yang; Wei, Kung-Hwa
Abstract : Correction for 'Twisted-graphene-like perylene diimide with dangling functional chromophores as tunable small-molecule acceptors in binary-blend active layers of organic photovoltaics' by Yu-Che Lin et al., J. Mater. Chem. A, 2021, DOI: ; 10.1039/d1ta05697b .